Interdependency between Nutrition and Oral Health - Shetty, Akshatha; Shetty, Pushparaja (Revista Cubana de Investigaciones Biomédicas, 2020)
It is a well-known fact that iron deficiency is the most common form of nutritional deficiency all over the world.Tooth pain or oral disease usually restricts the ability to eat healthy food and to alter nutritional levels and affect oral health, and so nutrition and oral health are interdependent. Dental caries is a preventable disease, and a better awareness of this disease through several more studies in this area is essential for the development of a comprehensive community dental prevention program